An Investigation of the Underlying Causes and Subsequent Consequences of Young Adult Pregnancy within the Rural Context of Mthatha, Eastern Cape - Kundlwana, Babalo; Asoba , Samson Nambei; Mefi, Nteboheng Patricia (Journal of Ecohumanism, 2025)
Background: Young adult pregnancy remains a pressing public health concern with profound implications for individuals, families, and communities. It is driven by a complex interplay of socioeconomic, educational, and psychological factors that necessitate in-depth, context-specific investigation to inform targeted interventions. Aim: The aim of this article was to investigate the underlying causes and subsequent consequences of young adult pregnancy within the rural context of Mthatha, Eastern Cape. Setting: The study was conducted in rural villages surrounding Mthatha, a region characterised by high unemployment, poverty, and limited access to health and educational resources. Methods: A qualitative research design was employed. Data were collected through in-depth, semi-structured interviews with young women who had experienced pregnancy. Participants were recruited using a snowball sampling strategy. Thematic analysis was used to interpret the data, focusing on recurring patterns and significant themes. Results: According to research, poverty is a major factor in early pregnancies and frequently forces young women to have transactional intercourse to meet their fundamental requirements. Additionally, a substantial knowledge gap about sexual and reproductive health was found, mostly because of insufficient or non-existent sex education. Early pregnancy has been linked to emotional suffering, social isolation, economic hardship, and interrupted educational trajectories. Many participants, especially those who were parenting their children as single mothers, expressed an acute lack of social and emotional support. Conclusion: Multifaceted interventions that address both structural and informational deficiencies are necessary to address young adult pregnancy. It is imperative to increase access to comprehensive reproductive health and sex education services. Contribution: This study advances knowledge on pregnancy among young adults in South African settings with limited resources. It emphasises the necessity of more research at broader provincial and national levels as well as the pressing need for community-level and policy-level solutions.